2018
DOI: 10.1007/s10544-018-0297-1
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte fouling on micro-engineered membranes

Abstract: Crossflow microfiltration of plasma from blood through microsieves in a microchannel is potentially useful in many biomedical applications, including clinically as a wearable water removal device under development by the authors. We report experiments that correlate filtration rates, transmembrane pressures (TMP) and shear rates during filtration through a microscopically high channel bounded by a low intrinsic resistance photolithographically-produced porous semiconductor membrane. These experiments allowed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The effect of different pore entrance angles can be seen as a link to the ‘membranes of the future’ that may have uniform pores, of which the actual geometry can be used to tune separation characteristics. Other example of areas that can benefit from our results are chromatography, injectable microgels for tissue engineering 26 and studies on blood cell flow 27 .…”
Section: Discussionmentioning
confidence: 95%
“…The effect of different pore entrance angles can be seen as a link to the ‘membranes of the future’ that may have uniform pores, of which the actual geometry can be used to tune separation characteristics. Other example of areas that can benefit from our results are chromatography, injectable microgels for tissue engineering 26 and studies on blood cell flow 27 .…”
Section: Discussionmentioning
confidence: 95%
“…Certain numbers of rigid cells are presumably trapped by the filter 1 in our two-step filtration. Red cell behaviors at the filter membrane surface depend on the perfusion pressure and pore size, i.e., deformable red cells dominate the pore resistance, whereas rigid cells roll and hesitate on the surface of filter membrane and then plug the pores 13) .…”
Section: Discussionmentioning
confidence: 99%
“…This is further proceeded with experiments to characterize the impact of filtration rates, transmembrane pressure, and shear rates to the dynamics of erythrocytes during the filtration process. It is found that erythrocytes tend to roll under low shear while settling under high filtration rates [273]. In one example, a microfluidic filtration platform with integrated rotary and bidirectional micro-pump has been used to separate WBCs from the whole blood with high efficiencies [262].…”
Section: Cross Flow Filtration Of Single Rbcs In Microchannelsmentioning
confidence: 99%